Bibliometric Analysis of Agribusiness Innovation in Scopus Publications 2010–2024 - Loso Judijanto (Westscience Press, 2026)
Agribusiness innovation has emerged as a critical driver of agricultural transformation, sustainability, and economic development in response to global challenges such as food insecurity, climate change, resource constraints, and technological disruption. The growing volume of scholarly publications in this field necessitates a systematic assessment of its intellectual structure and research evolution. Therefore, this study aims to analyze global research trends in agribusiness innovation through a bibliometric approach using publications indexed in the Scopus database from 2010 to 2024. Bibliographic data were collected from Scopus and analyzed using bibliometric performance indicators and science mapping techniques. VOSviewer was employed to visualize co-authorship networks, organizational collaborations, country collaborations, citation structures, keyword co-occurrences, overlay visualization, and density visualization. The results reveal a significant increase in publication output over the study period, indicating growing academic interest in agribusiness innovation. India emerged as the most influential country in terms of collaboration and research productivity, while several authors and institutions played important roles in shaping the field's intellectual development. Citation analysis highlights the importance of digital agriculture, sustainability, artificial intelligence, corporate social responsibility, and green innovation as major research foundations. Keyword mapping identifies agribusiness, agriculture, innovation, and sustainable development as the core themes, while smart agriculture, precision agriculture, machine learning, Internet of Things, and digital transformation represent emerging research directions. The findings demonstrate that agribusiness innovation research has evolved from a focus on competitiveness and entrepreneurship toward a broader integration of sustainability and advanced digital technologies. This study contributes to the literature by providing a comprehensive overview of the development, collaboration patterns, and thematic evolution of agribusiness innovation research and offers valuable insights for researchers, policymakers, and practitioners seeking to advance innovation-driven and sustainable agricultural systems.